2019
DOI: 10.1186/s12859-019-3161-2
|View full text |Cite
|
Sign up to set email alerts
|

Deep gene selection method to select genes from microarray datasets for cancer classification

Abstract: BackgroundMicroarray datasets consist of complex and high-dimensional samples and genes, and generally the number of samples is much smaller than the number of genes. Due to this data imbalance, gene selection is a demanding task for microarray expression data analysis.ResultsThe gene set selected by DGS has shown its superior performances in cancer classification. DGS has a high capability of reducing the number of genes in the original microarray datasets. The experimental comparisons with other representati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…For lung cancer diagnostic classifications, Podolsky et al 3 used support vector machine learning algorithms to perform lung cancer morphology classification. Alanni et al 4 developed a deep gene selection method to select genes from microarray datasets for cancer classification. Their experimental results showed that an average sensitivity of 95.22% and an average specificity of 77.39%.…”
Section: Introductionmentioning
confidence: 99%
“…For lung cancer diagnostic classifications, Podolsky et al 3 used support vector machine learning algorithms to perform lung cancer morphology classification. Alanni et al 4 developed a deep gene selection method to select genes from microarray datasets for cancer classification. Their experimental results showed that an average sensitivity of 95.22% and an average specificity of 77.39%.…”
Section: Introductionmentioning
confidence: 99%
“…Here, some tools are presented which are best matches with our task. Later in this research, some basics are covered to understand the work properly as depicted by the figure 1 from source [12].…”
Section: Motivationmentioning
confidence: 99%
“…In [4] RussulAlanni et al proposed an efficient gene selection algorithm. It can select relevant genes and significantly subtle to the samples in the few genes and less cost time by the algorithm achieved much high prediction accuracy on several public microarray data, it in turn proves the efficiency and effectiveness of the systems.…”
Section: Literature Surveymentioning
confidence: 99%
“…Carcinoma of the lungs, most commonly known as lung cancer is triggered due to the uninhibited growth of cell nodules in the lung tissues. [4] The survival rates of lung cancer are a very low percentage as compared to the other forms of cancer. It is considered a potentially life-threatening disease with a really high deathrate.…”
Section: Introductionmentioning
confidence: 99%